Profile of olanzapine long-acting injection for the maintenance treatment of adult patients with schizophrenia - Rosaria Di Lorenzo (Dove Medical Press, 2010)
Rosaria Di Lorenzo1, Alice Brogli21Department of Mental Health, AUSL-MODENA, Presidio Psichiatrico di Diagnosi e Cura 1, NOCSAE, Baggiovara, Modena, Italy; 2School of Specialization in Psychiatry, University of Modena e Reggio Emilia, Modena, ItalyAbstract: Olanzapine long-acting injection (OLAI) is a crystalline salt composed of olanzapine and pamoic acid, which permits a depot intramuscular formulation of olanzapine. The half-life of olanzapine pamoate is 30 days, and its steady state is reached approximately at 12 weeks. Oral supplementation of olanzapine is not required during OLAI initiation, according to Eli Lilly recommendations, although a study indicated that ≥60% of D2 receptor occupancy was reached only by the fifth injection cycle. To date, a short-term, placebo-controlled study of 8 weeks in acutely ill patients and a long-term, controlled trial of 24 weeks in stabilized patients have been conducted. In both the studies, efficacy and safety were similar to those of oral olanzapine, with the exception of an acute adverse effect, the so-called inadvertent intravascular injection event, which occurred 1–3 hours after the injection with an incidence rate of 0.07% per injection. It consisted of symptoms that are similar to those reported in cases of oral olanzapine overdose. The most significant studies published to date, on the use of olanzapine pamoate in schizophrenia, are reviewed in this article. The pharmacodynamic and pharmacokinetic profile and related side effects of OLAI are reported.Keywords: olanzapine pamoate long-acting injection, efficacy, safety